Řízení vytápění rodinného domu - Hnyk, Marek (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2016)
Cílem diplomové práce je návrh a implementace systému, který bude umožňovat ovládání vytápění na základě údajů získaných monitorováním jednotlivých místností v objektu. Zvláště se zaměřte na oblast měření teploty vody v systému topení, TUV a teploty v prostoru obytných místností. Ústředna musí umožňovat automatické ukládání měřených hodnot. Vybrané hodnoty teploty budou zpřístupněny pomocí webového rozhraní a průběžně ukládány na webový server.

The aim of the final thesis is a proposal and implementation of a system which would enable a heating control on the basis of data gathered by monitoring of particular rooms inside a building. In particular, it is focused on water measurement within the heating system, TUV (non-potable hot water) and the temperature within the space of residential rooms. The system headquarters must enable an automated saving of the measured data. Selected temperature figures will be made accessible by a web interface and continuously saved on the web server.
Control of house heating
Keywords: Měření teploty; dálkové ovládání; senzor teploty; automatizace vytápění.; Measuring of temperature; remote kontrol; temperature sensor; automatizacion of heating.